Continuum flow model of MHD Casson nanofluid over a rotating disk with multiple slips - Khuram Rafique; Aisha M. Alqahtani; Ayesha Rehman; Najla A. Mohammed; Ilyas Khan (Partial Differential Equations in Applied Mathematics, 2025)
The present study articulates the various features of Casson nanofluid flow over a rotating disk along Brownian motion and thermophoresis effects. In addition the influences of thermal radiations along with Sore effect are taken in to account. Due to the poor thermal performance of conventional fluids, the nanoliquid has attained great importance in heat transmission phenomenon and other industrial and engineering applications in current era. The motivation behind this study is its significance relevance in various technological and engineering applications. The governing flow equations are transformed into nonlinear ODE's by adopting suitable similarity transformations. The Keller box technique is utilized to find the numerical outcomes of the resulting nonlinear ODE's. Graphs illustrated that how non-dimensional physical factors affect the velocity, temperature and concentration patterns. From graphical results, we found the thermal slip slows down the velocity of the liquid. Moreover, the temperature distribution diminishes with the increment in velocity slip factor.